2021
DOI: 10.1186/s40246-021-00372-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel signature based on unfolded protein response-related gene for predicting prognosis in bladder cancer

Abstract: Background The unfolded protein response (UPR) served as a vital role in the progression of tumors, but the molecule mechanisms of UPR in bladder cancer (BLCA) have been not fully investigated. Methods We identified differentially expressed unfolded protein response-related genes (UPRRGs) between BLCA samples and normal bladder samples in the Cancer Genome Atlas (TCGA) database. Univariate Cox analysis and the least absolute shrinkage and selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…We found increased CALR expression in BCA which correlated with poor prognosis ( Figure 2B ). This is consistent with all reported findings ( Liu et al, 2020 ; Zhu et al, 2021 ). The results of our in vitro experiments validated that the mRNA expression of CALR was higher in BCA cells T24 than in normal urothelial cells SV-HUC-1 ( Figure 9B ); upon knocking down the gene expression of CALR in T24 cells, the viability of tumor cells reduced significantly ( Figure 9D ), a phenomenon consistent with the clinical outcomes.…”
Section: Discussionsupporting
confidence: 94%
“…We found increased CALR expression in BCA which correlated with poor prognosis ( Figure 2B ). This is consistent with all reported findings ( Liu et al, 2020 ; Zhu et al, 2021 ). The results of our in vitro experiments validated that the mRNA expression of CALR was higher in BCA cells T24 than in normal urothelial cells SV-HUC-1 ( Figure 9B ); upon knocking down the gene expression of CALR in T24 cells, the viability of tumor cells reduced significantly ( Figure 9D ), a phenomenon consistent with the clinical outcomes.…”
Section: Discussionsupporting
confidence: 94%
“…Genetic biomarkers would be viable to represent heterogeneity among BC, predicting the sensitivity of urothelial neoplasms tissues toward platinum. Previous studies have reported several prognostic gene signatures that are related to tumor microenvironment, immune cell infiltrating, unfolded protein response, and so on ( 40 42 ). However, signature associated with platinum-based chemotherapy resistance has not been recorded yet.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic biomarkers would be viable to represent heterogeneity among BC, thus predicting the sensitivity of urothelial neoplasms tissues toward platinum. Previous studies have reported several prognostic gene signatures that are related to tumor microenvironment, immune cell in ltrating, unfolded protein response, and so on [39][40][41] . But signature that is associated with platinum-based chemotherapy resistance has not been recorded yet.…”
Section: Discussionmentioning
confidence: 99%